ASSESSING THE DETERMINANTS OF EFFICIENT STEEL STRUCTURE ERECTION IN THE BUILDING INDUSTRY - Morgan Iteji, Olokpo (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2023)
The presence of steel structures significantly impacts the ecosystem of building construction. However, in order to have a successful erection of steel structures, many factors steel erectors and contractors must take into consideration. As a result, this study aims to investigate the factors that influence the erection of steel structures in the construction industry. This study adopted a survey research method to ascertain the determinants of efficient steel structure erection in the building industry. A convenient sample of fifty-five (55) project managers, project engineers, and site engineers involved in the erection of steel structures in Edo State, Nigeria, participated in the study. The analysis indicated that funding (23.13%) represents the primary factor affecting steel erection. Followed by manpower (20.21%), equipment (16.12%), project type (13.16%), and management (13.11%), while safety measures (12.92%) ranked as the lowest factor affecting steel structure erection in the building industry. The findings provide an in-depth insight into the factors affecting steel structure erection in a construction project that can help project managers develop strategies for improving the erection of steel structures in the construction industry.